PREFABRICATRED VERTICAL DRAIN IMPROVED SOFT SOIL USING THREE-DIMENSIONAL FINITE ELEMENT METHOD - Gilang Ramadan Kololikiye; Yulvi Zaika; Harimurti Harimurti (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2021)
The subgrade layer of freeway construction in East Java contains high compressibility of soft soil with 24.5 m depth and 10.2 m height of the embankment. It is necessary to stabilize using PVD by accelerating the process of consolidation to increase its bearing capacity. In this study, 3D FEM programming is used to analyze the consolidation in pursuing to compare with the analytical results. 3D FEM shows the settlement without PVD is 0.834 m with excess pore water -4 kN/m2, while using PVD the settlement 0.819 m with excess pore pressure -8 kN/m2. For the analytical results, both variations indicate the settlement 0.787 m. It’s because the FEM discretization analyzed in 3D gives more accurate results.